Advances on sonophotocatalysis as a water and wastewater treatment technique: efficiency, challenges and process optimisation - Mapukata, Sivuyisiwe; Ntsendwana, Bulelwa; Mokhena, Teboho; Sikhwivhilu, Lucky (Frontiers in Chemistry, 2023)
Due to water shortage and increased water pollution, various methods are being explored to improve water quality by treating contaminants. Sonophotocatalysis is a combination of two individual water treatment processes i.e. photocatalysis and sonocatalysis. With advantages including shorter reaction times and enhanced activity, this technique shows possible futuristic applications as an efficient water treatment technology. Herein, background insight on sonophotocalysis as a water and wastewater treatment technique as well as the general mechanism of activity is explained. The commonly used catalysts for sonophotocatalytic applications as well as their synthesis pathways are also briefly discussed. Additionally, the utilization of sonophotocatalysis for the disinfection of various microbial species as well as treatment of wastewater pollutants including organic (dyes, pharmaceuticals and pesticides) and inorganic species (heavy metals) is deliberated. This review also gives a critical analysis of the efficiency, enhancement strategies as well as challenges and outlooks in this field. It is thus intended to give insight to researchers in the context of facilitating future developments in the field of water treatment, and advancing sonophotocatalysis towards large-scale implementation and commercialization.